2015
DOI: 10.1167/iovs.15-16854
|View full text |Cite
|
Sign up to set email alerts
|

Increased sCD200 Levels in Vitreous of Patients With Proliferative Diabetic Retinopathy and Its Correlation With VEGF and Proinflammatory Cytokines

Abstract: Expression of sCD200 may contribute to retinal angiogenesis by interacting with VEGF-mediated inflammatory response and represents a potential therapeutic target for the patients with PDR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…In addition, blood-circulating leukocytes may engage with adhesion molecules, such as intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule (VCAM) and selectins, on the surface of endothelial cells, and the adherence of these cells to the endothelial wall may result in the occlusion of capillaries (leukostasis). Such vascular–immune cell interactions contribute to microvascular damage by releasing cytokines and superoxide via respiratory burst, which alters the integrity of the NVU [ 28 , 29 ]. In the advanced stages of diabetic retinopathy, in which immune privilege is compromised, circulating immune cells and serum proteins may infiltrate the retina and vitreous, thus participating in chronic inflammation and retinal vascular and neuronal damage [ 30 ].…”
Section: Is Microvascular Disease a Primary Pathogenic Event In The Dmentioning
confidence: 99%
“…In addition, blood-circulating leukocytes may engage with adhesion molecules, such as intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule (VCAM) and selectins, on the surface of endothelial cells, and the adherence of these cells to the endothelial wall may result in the occlusion of capillaries (leukostasis). Such vascular–immune cell interactions contribute to microvascular damage by releasing cytokines and superoxide via respiratory burst, which alters the integrity of the NVU [ 28 , 29 ]. In the advanced stages of diabetic retinopathy, in which immune privilege is compromised, circulating immune cells and serum proteins may infiltrate the retina and vitreous, thus participating in chronic inflammation and retinal vascular and neuronal damage [ 30 ].…”
Section: Is Microvascular Disease a Primary Pathogenic Event In The Dmentioning
confidence: 99%
“…The concentrations of VEGF-B and NLRP3 were below the limit of ELISA detection, thus the two cytokines were not included. The upregulated cytokines in PDR vitreous were also compared with publications (25)(26)(27)(28)(29) (Supplementary Table 1). Here, we identified 23 cytokines that significantly upregulated in PDR vitreous compared to control (Figure 6A).…”
Section: Profibrotic and Fibrogenic Phenotype Of Microglia Orchestrates The Progression Of Fvm Formationmentioning
confidence: 99%
“…This study also showed that vitreous levels of sCD200 are higher in PDR patients with DME (266.9 ± 28.82 pg/mL) or traction retinal detachment (TRD) (256.9 ± 34.50 pg/mL) compared to PDR patients without DME (136.9 ± 15.13 pg/mL) or TRD (146.9 ± 15.97 pg/mL). sCD200 level increases also have significant statistical correlations with the increase of several angiogenic and inflammatory molecules such as VEGF, IL-6, IL-8 and IL-10 [115].…”
Section: Soluble Cd200mentioning
confidence: 89%
“…CD200 exists in a cell membrane-bound form and a soluble form. It exerts inhibitory effects on microglia/ macrophages via interaction with the CD200 receptor (CD200R) [115]. DR-related neuronal degeneration also reduces CD200 concentration and further induces microglial activation [6].…”
Section: Soluble Cd200mentioning
confidence: 99%